Pharmacodermia in a dog of the Dalmatian breed: Case report - Guimarães, Claudio; Guimarães, Claudio; Carvalho, Caio; Aires, Ene; Carneiro, Mário; David, Maridelzira; Moreira, Luiz (Pubvet, 2018)
It is understood as pharmacodermia the hypersensitivity reaction to certain drugs manifested by focal or diffuse dermatological lesions. This paper presents a case of pharmacodermia in dogs after administration of amoxicillin associated with potassium clavulanate. A Dalmatian dog, male, one year and five months old, weighing 33kg was attended at the Veterinary Hospital Professor Mário Dias Teixeira of the Federal Rural University of the Amazon, having as main complaint the presence of constipation about two months ago. From clinical examination and imaging studies it was observed that the patient had narrowing of the rectal ampulla, prostatic cysts and cystitis, and therapeutic anoplasty and orchiectomy were recommended. Tramadol hydrochloride, meloxicam, and amoxicillin associated with potassium clavulanate were instituted for the pre and postoperative period. The presence of scaly lesions on the skin and signs of secondary bacterial infection, mainly concentrated in the lumbar region, was observed on the ninth postoperative day. Meloxicam was replaced by ketoprofen and treatment with amoxicillin and clavulanate was maintained for another five days. After this period, the patient returned with lesion evolution, emaciation and hypophagia. Due to the evolution of the case, clinical history and presentation of the lesions, pharmacodermia was suspected. Subsequently, amoxycillin was replaced with ciprofloxacin and surgical debridement of the lesions. Finally, after surgical treatment, regression of lesions with a good healing process was observed, suggesting that the case may be a pharmacological.